Etnomatematika dalam Ungkapan Bahasa Lokal Pattinjo: Memahami Konsep Geometri melalui Perspektif Budaya - Khaeri, Ummi; Usman, Usman; Rahman K, Abd (Journal of Mathematics Learning Innovation, 2024)
This research departs from the framework that culture is a tool that can be used as a basic ingredient in learning activities, this activity is known as ethnomathematics. The concept of geometry includes the subject matter of the scientific field of mathematics which is closest to real-world problems. Therefore, this study aims to examine language expressions that contain the concept of geometry, as language is one of the elements in a culture. This research uses a type of qualitative research with an ethnographic approach as it means that this research focuses on research on the behavior and culture of a group, in this case based on observation, interviews conducted with community leaders who understand the Pattinjo language well to help translate terms that contain concept geometry, and documentation. The research results obtained indicate that there are a number of mathematical languages ​​used by the Pattinjo people in their daily activities that contain the concept of geometry. Mathematical language includes the mention of the names of objects that have elements of plane shapes and spatial shapes, expressions of terms in the mention of area, height, volume, and numbers. It is hoped that the data obtained as a result of the research can open the public's view, especially to students, that cultural elements, namely local languages, can be used as a context that can be used as a starting point in learning mathematics.